MITOS KECANTIKAN DALAM NOVEL YOU MATTER KARYA PURI VIERA - Khalida Chairunnisa (Prosiding Seminar Nasional Sasindo, 2022)
This study examines the myth of beauty in the novel You Matter by Puri Viera. The purpose of this study is to describe the myth of beauty and to describe efforts to redefine the myth of beauty in the novel You Matter by Puri Viera. The theory used in this study uses the beauty myth theory formulated by Naomi Wolf. The research data was collected using a literature study technique method, then the data would be analyzed in a way that was clearly described and then the meaning would be interpreted. Based on the results of the study, it was found that the beauty myths in Puri Viera's novel You Matter consist of objective and universal beauty, beauty as a male institutional issue, beautiful behavior, Professional Beauty Qualification, and efforts to redefining beauty myths carried out by Puri characters. The beauty myth can be seen from the words of Puri's character who compares herself to her friends who are considered beautiful, where Puri is often considered not beautiful by those closest to her because her physique does not meet the existing ideal beauty standards. The Puri figure fought against the beauty myth, so that it emerged as an attempt to redefining the beauty myth. Thus, it can be concluded that the Puri Character initially accepted the beauty myth, then eventually changed his mind and rejected the existence of the beauty myth.Keywords: Feminism, Beauty Myth, Naomi Wolf